Faktor-Faktor yang Mempengaruhi Motivasi Belajar pada Mata Pelajaran Teknik Bubut Kelas XI Jurusan Teknik Pemesinan di SMK Negeri 1 Padang - Aldo Ramadhana; Refdinal Refdinal; Purwantono Purwantono; Randi Purnama Putra (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This study aims to analyze the factors that influence students' learning motivation in the Lathe Engineering subject in class XI of the Department of Machining Engineering at SMK Negeri 1 Padang. Several variables studied include learning interest, ideals, friendship environment, and family environment, each of which acts as an independent variable, while learning motivation functions as a dependent variable. The method used in this study is quantitative with a correlational approach, where the research sample consisted of 51 students selected using a saturated sampling technique, namely sampling that covers the entire population in the class. The instrument used in this study was a questionnaire with a Likert scale that has been tested for validity and reliability to ensure that the measuring instrument used is able to extract accurate and consistent data. The data obtained were then analyzed using multiple linear regression techniques with the help of SPSS version 26 to determine the effect of each variable on student learning motivation. The results of the study indicate that partially, learning interest and friendship environment have a significant influence on student learning motivation. Students who have a high interest in the Lathe Engineering subject tend to have better learning motivation, and positive relationships with their friends also increase their enthusiasm for learning. In contrast, the variables of ideals and family environment did not show a significant influence on students' learning motivation in the context of this study. Although ideals and family support are often considered important factors in education, the results of this study indicate that external factors such as friendships are more dominant in influencing students' learning motivation. Simultaneously, all four variables significantly influenced students' learning motivation, with the friendship environment being the most dominant factor.